From charity to capital: Indonesia’s Islamic social finance surge and the case for blended finance - Sahara Putri Dahlan (Journal of Islamic Economic Insights, 2026)
Indonesia’s Islamic social finance is entering a new phase of development. The national collection of zakat, infaq, and sadaqah channelled through the zakat system reached approximately IDR 52.5 trillion by the second quarter of 2025, a 43% year-on-year increase, while the outstanding value of Cash Waqf Linked Sukuk (CWLS)—a hybrid instrument that fuses Islamic endowment with sovereign sukuk—grew by roughly 22% (Bank Indonesia, 2026). This commentary reads the surge and rise of blended commercial-social instruments such as CWLS as a movement from charity toward productive, capital-market-integrated social finance—the feature that most sharply distinguishes an Islamic economy from a conventional one. Drawing on Scopus- and Web of Science–indexed scholarship, the article argues that this is Indonesia’s most distinctive and promising frontier, but that the gap between realized and potential remains vast (national zakat potential is estimated at IDR 327 trillion, while realized cash waqf stood at only about IDR 2.9 trillion), that governance, fragmentation, and low literacy constrain scale, and that the strategic prize is genuine integration of commercial and social finance rather than parallel operation. It contends that blended instruments must be judged by measurable socioeconomic impact, not merely by the funds they mobilize for.